Novel Strategy for Preparing Dual-Modality Optical/PET Imaging Probes via Photo-Click Chemistry - Sun, Lingyi (Bioconjug Chem, 2016)
Preparation of small molecule based dual-modality probes remains a challenging task due to the complicated synthetic procedure. In this study, a novel concise and generic strategy for preparing dual-modality optical/PET imaging probes via photo-click chemistry was developed, in which the diazole photo-click linker functioned not only as a bridge between the targeting-ligand and the PET imaging moiety, but also as the fluorophore for optical imaging. A dual-modality AE105 peptidic probe was successfully generated via this strategy and subsequently applied in the fluorescent staining of U87MG cells and the (68)Ga based PET imaging of mice bearing U87MG xenograft. In addition, dual-modality monoclonal antibody cetuximab has also been generated via this strategy and labeled with (64)Cu for PET imaging studies, broadening the application of this strategy to include the preparation of macromolecule based imaging probes.